Shifting analysis of grain carriers using System Dynamics Simulation - Ekawati, Ratna; Wahyuni, Nuraida; Anjani, Fitri (Rekayasa, 2024)
PT PFS is a subsidiary of PT BJ specially serving of port services. PT PFS need to shift FSO Ardjuna Sakti from jetty 1.6-1.7 to the new jetty (jetty 4.5-4.6) because PT PFS has some problems and activity plans. The problems are teh increased of commercial demand, the development jetty 3 of port CDG, the Berth Occupation Ratio (BOR) which already exceeds 65%, the expansion plan of PT BJ and the need for flexibility on the jetty 1.5-1.8. Therefore, it is necessary to do the analysis of shifting the FSO Ardjuna Sakti. The method use in this study is comparing the financial analysis using manual calculation and system dynamics simulation. The financial analysis uses in this study are Internal Rate of Return (IRR), Payback Period, Net Present Value (NPV) and comparing revenue and profit between FSO Ardjuna Sakti in jetty 1.6-17 and jetty 4.5-4.6. The result of the study showed that the IRR is 14,73%, it is exceed than the MARR of BI rate 6,5%, Payback Period is 5 years so investment will comeback at 5 next years, and the value of the NPV with manual and system dynamics simulation has both positive value or exceed than 0 (zero). The result of manual calculation of NPV is Rp.15.369.374.455 and the result of system dynamics simulation is Rp.1.184.863.983.489. Comparing manual calculation and system dynamics simulation of revenue and profit of FSO Ardjuna Sakti in jetty 1.6-1.7 respectively is Rp.2.384.292.880 and Rp.2.125719.660 whilst in jetty 4.5-4.6 respectively is Rp.9.015.993.344 and Rp.6.761.995.008. From those financial methods compared manually and by system dynamics simulation, we can conclude the investment decisions are feasible. And activity of shifting FSO Ardjuna Sakti from jetty 1.6-1.7 to the jetty 4.5-4.6 is appropriate to do.